2021
DOI: 10.1101/2021.01.09.21249505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wastewater Virus Detection Complements Clinical COVID-19 Testing to Limit Spread of Infection at Kenyon College

Abstract: In-person college instruction during the 2020 pandemic required effective and economical monitoring of COVID-19 prevalence. Kenyon College and the Village of Gambier conducted measurement of SARS-CoV-2 RNA from the village wastewater plant and from an on-campus sewer line. Wastewater RNA detection revealed virus prevalence leading to individual testing and case identification. Wastewater surveillance also showed when case rates had subsided, thus limiting the need for individual clinical testing. Overall, wast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Analyses performed by partners of the OWMN using Ohio's data indicated that the monitored sites showed significant correlation between SARS-CoV-2 concentrations in wastewater and new case counts in monitored communities 14,28,29…”
Section: Contextmentioning
confidence: 99%
“…Analyses performed by partners of the OWMN using Ohio's data indicated that the monitored sites showed significant correlation between SARS-CoV-2 concentrations in wastewater and new case counts in monitored communities 14,28,29…”
Section: Contextmentioning
confidence: 99%
“…Currently, several public and private organizations are conducting building surface surveillance and developing data-driven action plans. During the COVID-19 pandemic, many academic institutions ( Betancourt et al, 2020 ; Barich and Slonczewski, 2021 ; Gibas et al, 2021 ; Harris-Lovett et al, 2021 ) and jurisdictional authorities ( Gonzalez et al, 2020 ; Larsen and Wigginton, 2020 ; Medema et al, 2020 ; Peccia et al, 2020 ) around the globe rapidly developed and deployed wastewater and building air HVAC surveillance tools ( Hermesch et al, 2020 ; Horve et al, 2020 ). These data sets provide the opportunity to develop best practices and validate sample collection and processing methods.…”
Section: Identified Capacity Needs and Opportunities For Coordinated Science And Technology Investmentmentioning
confidence: 99%
“…Additionally, in the absence of widespread clinical testing, WBE can act as a health surveillance tool to monitor viral dynamics, as it has been shown to presage new case and subsequent hospitalization rates [ 22 , 25 ]. Accordingly, numerous higher educational institutions have adopted building-level wastewater testing in combination with contact tracing and isolation/quarantine protocols to support campus public health and guide clinical testing resources to “hotspot” locations [ 25 , 26 , 27 , 28 , 29 , 30 ]. Due to its ability to capture population-level health information, WBE will continue to serve as a valuable means to monitor and inform public health programming and response.…”
Section: Introductionmentioning
confidence: 99%